The Neglected Uterine NK Cells/Hamperl Cells/Endometrial Stromal Granular Cell, or K Cells: A Narrative Review from History through Histology and to Medical Education - Lapides, Lenka; Varga, Ivan; Csöbönyeiová, Mária; Klein, Martin; Pavlíková, Lada; Visnyaiová, Kristína; Babál, Pavel; Mikušová, Renáta (International journal of molecular sciences, 2023)
Reproductive immunology is at the forefront of research interests, aiming to better understand the mechanisms of immune regulation during gestation. The relationship between the immune system and the implanting embryo is profound because the embryo is semi-allogenic but not targeted by the maternal immune system, as expected in graft-versus-host reactions. The most prominent cell population at the maternal-fetal interface is the population of uterine natural killer (uNK) cells. Uterine NK cells are two-faced immunologically active cells, bearing comparison with Janus, the ancient Roman god of beginnings and endings. Their first face can be seen as natural killer cells, namely lymphocytes, which are critical for host defense against viruses and tumors. Even though uNK cells contain cytolytic molecules, their cytotoxic effect is not applied to classical target cells in vivo, playing a permissive rather than a defensive role. Their second face is crucial in maintaining physiological gestation-uNK cells show critical immunomodulatory functions with the potential to control embryo implantation and trophoblast invasion, regulate placental vascular remodeling, and promote embryonic/fetal growth. Therefore, we believe that their current designation "natural killer cells" (the first "cytotoxic" Janus's face) is misleading and inappropriate, considering their principal function is supporting and maintaining pregnancy. In this narrative review, we will focus on three lesser-known areas of knowledge about uNK cells. First, from the point of view of histology, we will comprehensively map the history of the discovery of these cells, as well as the current histological possibilities of their identification within the endometrium. To be brief, the discovery of uNK cells is generally attributed to Herwig Hamperl, one of the most influential and prominent representatives of German pathology in the 20th century, and his co-worker, Gisela Hellweg. Secondly, we will discuss the interesting aspect of terminology, since uNK cells are probably one of the human cells with the highest number of synonymous names, leading to significant discrepancies in their descriptions in scientific literature. From the first description of this cell type, they were referred to as endometrial granulocytes, granular endometrial stromal cells, or large granular lymphocytes until the end of the 1980s and the beginning of the 1990s of the last century, when the first publications appeared where the name "uterine NK cells" was used. The third area of present review is medical teaching of histology and clinical embryology. We can confirm that uNK cells are, in most textbooks, overlooked and almost forgotten cells despite their enormous importance. In the present narrative review, we summarize the lesser-known historical and terminological facts about uNK cells. We can state that within the textbooks of histology and embryology, this important cell population is still "overlooked and neglected" and is not given the same importance as in fields of clinical research and clinical practice.
Keywords: Pregnancy; Placenta; Terminologia Histologica; Endometrium; immunohistochemistry; Humans; studium lékařství; Female; Hamperl cells; medical education; uterine NK cells; ženské pohlaví; Uterus; buňky NK; Killer Cells, Natural; placenta; endometrium; histology; uterus; lidé; těhotenství; Education, Medical